2015
DOI: 10.1371/journal.pone.0137055
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with HIV Prevalence and HIV Testing in Sierra Leone: Findings from the 2008 Demographic Health Survey

Abstract: BackgroundThe Sierra Leone Demographic Health Survey 2008 found an HIV prevalence of 1.5%. This study investigates associations with HIV infection and HIV testing.MethodsHouseholds were selected using stratified multi-stage sampling. In all selected households women aged 15–49 were eligible. In every second household men aged 15–59 were also eligible. Participants were asked to consent for anonymous HIV testing. All participants interviewed and tested were analysed. Multiple logistic regression identified asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 23 publications
10
30
1
Order By: Relevance
“…The result of this study coincides with findings of other many studies [2,3,[13][14][15]31,40,41]. Studies found that the reason for HIV testing uptake among females was accepting testing when it is offered, while among males it was voluntary testing [31] and significantly determined by the individual's economic status, behavior and knowledge of HIV/AIDS [42].…”
Section: Journal Of Transmitted Diseases and Immunity Issn 2573-0320supporting
confidence: 90%
See 4 more Smart Citations
“…The result of this study coincides with findings of other many studies [2,3,[13][14][15]31,40,41]. Studies found that the reason for HIV testing uptake among females was accepting testing when it is offered, while among males it was voluntary testing [31] and significantly determined by the individual's economic status, behavior and knowledge of HIV/AIDS [42].…”
Section: Journal Of Transmitted Diseases and Immunity Issn 2573-0320supporting
confidence: 90%
“…Though similar data was not available in the DHS data files of Gabon, the main reasons for HIV test uptake among Cameroonian youth were found to be asked for the test, offered and accepted, and required which indicates their low awareness, as they did not do it voluntarily. However, a welcoming achievement was found in receiving results of HIV testing which is higher than in many African countries [3]. The causes for the decreased awareness and HIV test uptake among youth can be many, for example, their own lack of knowledge and information about HIV/AIDS [38], limitations of the countries to provide the services due to some shortages like human, financial, material and technical resources and others like inadequate involvement of community volunteers or spiritual (1) knowing that both condom use and limiting sex partners to one uninfected faithful partner are HIV prevention methods, (2) being aware that a healthy looking person can have the AIDS virus, and (3) rejecting two most common local misconceptions (the two most common local misconceptions in Cameroon and Gabon were; that the AIDS virus can be transmitted through mosquito bites, and by supernatural means).…”
Section: History Of Hiv Test Experiences Among Youthmentioning
confidence: 99%
See 3 more Smart Citations